1. x + 4 = 28
x + 4 – 28
x = 24
2. y - 6.5 = 31
y = 31 + 6.5
y = 37.5
3. 8z = 40 + 3z
8z - 3z = 40
5z = 40
z = 40
5
z= 8
4. 10x = -5x + 60
10x + 5x = 60
15x = 60
x = 60
15
x = 4
5. -15y + 3 = -36 - 18y
-15y + 18y = -36 - 3
3y = -39
y = -39
3
y = -13
6. 2x + 4 + (3x - 4) = 3x + 12
2x + 4 + 3x - 4 = 3x + 12
2x + 3x + 3x = 12 - 4 + 4
2x = 12
x = 12
2
x = 6
7. 4 ( 3x + 2) - 8 = 5 (2x + 3) + 5
12x + 8 - 8 = 10x + 15 + 5
12x - 10x = 15 + 5 - 8 + 8
2x = 20
x = 20
2
x = 10
8. 15x - 40 - 5x - 20 = 0
15x - 5x = 40 + 20
10x = 60
x = 60
10
x = 6
9. 16 - (-2x - 4) - (5x - 3x + 2) = -4x - (-8x + 2)
16 + 2x + 4 - 5x + 3x - 2 = -4x + 8x - 2
2x - 5x + 3x + 4x - 8x = -2 - 16 - 4 + 2
-4x =-20
x = -20
-4x = 5
10. - ( 7x - 2 + 12) + (-5x - 3x + 4) = - (-x + 7) - (6x - 4 - 7)
-7x + 2 - 12 - 5x - 3x + 4 = x - 7 - 6x + 4 + 7
-7x - 5x - 3x - x + 6x = -7 + 4 + 7 - 2 + 12 - 4
-10x = 10
x = 10
-10
x = -1
11. -18 - [3(x + 2) + 4] = 21 - [6 (-2x - 2) + 1]
-18 - [3x + 6 + 4] = 21 - [ -12x - 12 + 1]
-18 -3x -6 -4 = 21 + 12x + 12 - 1
-3x-12x = 21 + 12 - 1 + 18 + 6 + 4
-15x = 60
x = 60
-15
x = -4
No hay comentarios:
Publicar un comentario